Le Style : Tours Multiple - Association Tours Art Vivant, Tours; Baruchello, Gianfranco; Ben; Borer, Alain; Breton, David Le; Burke, Alex; Ceccarelli, Jean-Jacques; Cueco, Henri; Cyroulnik, Philippe; Errò; Ferrat, Dominique; François, Yannick; et al. (Tours : Tours Multiple, 1981)
Adami, Valerio ; Baruchello, Gianfranco ; Ben ; Burke, Alex ; Ceccarelli, Jean-Jacques ; Champion-Métadier, Isabelle ; Cueco, Henri ; Errò ; Ferrat, Dominique ; François, Yannick ; frebot, Jacques ; Galliani, Omar ; Gerard, Michel ; Gramatzki, Eve ; Haas, Michel ; Isnard, Vivien ; Jaccard, Christian ; Lanneau, Patrick ; Limérat, Francis ; Mahdavi, Rafael ; Mahé, Guy ; Mondino, Aldo ; Monory, Jacques ; Pagès, Bernard ; Saulnier, Emmanuel ; Zuber, Jean
biografie
Le Style, Tours Multiple, Tours (France), 20 mars - 27 avril 81
Frans
kunstcatalogus